Modernization of pedagogical education in Russia: experience and prospects. (Journal of Educational Sciences, 2016)
The article reflects the Russian experience of reforming teacher education, generalizes some of the trends of development. Structure of the paper includes: introduction; topics – research of actual qualities of the modern school teacher; stimulation of innovation activities in the school; and conclusion. Are the data of the questionnaire survey to identify the actual qualities of the modern school teacher. The actual quality of the teacher: «social responsibility (liability for knowledge, life, the future of children)»; «inspiration»; «the capacity for innovation and skills»; «informationculture»; «adaptability to the social environment». Examined the practice obtain master’s degree on a specialty «Pedagogic and psychology» to extend the psychological and pedagogical competences of teachers. The authors found that the master program «Pedagogy and psychology»attracts entrants graduate teachers for the expansion of psychological training. Attention is focused on tendencies of strengthening of the state policy in the field of education. Highlighted the trend of de-monopolization of the state in education. Education management in the immediate short term should become a public-private. Russian experts in the nearest future, expect Association of higher and additional professional pedagogical education based on the principles of network interaction, personalization of educational services, deepening integration withclassical and technical universities, on the one hand, and with a comprehensive school.
Keywords: pedagogical education; master’s degree; teacher; school; training teachers